2018
DOI: 10.1080/00313831.2017.1415968
|View full text |Cite
|
Sign up to set email alerts
|

Talk About Field Placement Within Campus Coursework: Connecting Theory and Practice in Teacher Education

Abstract: Worldwide, scholars and policymakers have called for teacher education to link fieldwork and coursework. This article examines teacher candidates' opportunities to talk about field placement within their campus coursework as one way of doing so. It reports on survey data (n = 270) and observation data (n = 52 hours) from three teacher-education programs in Norway, Finland, and California in the United States. Findings suggest that candidates have extensive opportunities to talk about field placement. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 44 publications
2
6
0
3
Order By: Relevance
“…Uni2 candidates reported more coherence between their courses and their field placement than the Nordic candidates. This aligns with findings from a study by Jenset, Hammerness, and Klette (2017) using observation data. They found that candidates from the Uni2 program reported significantly more opportunities to link their experiences from their field placement to theory compared with candidates from the Uni1 or Uni3 program.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Uni2 candidates reported more coherence between their courses and their field placement than the Nordic candidates. This aligns with findings from a study by Jenset, Hammerness, and Klette (2017) using observation data. They found that candidates from the Uni2 program reported significantly more opportunities to link their experiences from their field placement to theory compared with candidates from the Uni1 or Uni3 program.…”
Section: Discussionsupporting
confidence: 90%
“…They found that candidates from the Uni2 program reported significantly more opportunities to link their experiences from their field placement to theory compared with candidates from the Uni1 or Uni3 program. Likewise, Jenset et al’s (2017) study supported our finding that the candidates from both Nordic programs perceived an equal extent of coherence between courses and field placement. There, candidates from the Uni1 and Uni3 program reported a similar amount of opportunities to discuss experiences from their own fieldwork in their classes.…”
Section: Discussionsupporting
confidence: 86%
“…Relevans er noe man skaper ved å bruke og forklare hvordan teorier kan brukes, som grunnlag for og refleksjon over profesjonsutøvelse. Imidlertid viser tidligere forskning at laererstudenter kan synes det er vanskelig å se relevans av og sammenheng mellom det de laerer på campus og det de laerer ved skolene i praksisperiodene (Grossman, Hammerness, McDonald & Ronfeldt, 2008;Hatlevik & Smeby, 2015;Jenset, Hammerness & Klette, 2019;Smeby & Heggen, 2014). Å gjøre kunnskapsinnholdets relevans tydelig for studentene kan derfor sees som en sentral utfordring for laererutdanningen.…”
Section: God Laererutdanningunclassified
“…A particular concern has been how learning across sites can be better aligned and how schools can be positioned as equal partners in teacher qualification (Grossman, Hammerness, McDonald, & Ronfeldt, 2008;Lillejord & Børte, 2016;Zeichner, 2010). This literature emphasises closer cooperation between higher education institutions and schools, and the need to organise on-campus learning activities around teachers' practices (Canrinus, Klette, & Hammerness, 2017b;Darling-Hammond, 2014;Forzani, 2014;Jenset et al, 2018;Windschitl, Thompson, Braaten, & Stroupe, 2012). Within this body of research, the notion of integration often has a spatial framing, examining the interrelationship between two sites of learning (e.g.…”
Section: Coherence and Knowledge Integration In Teacher Educationmentioning
confidence: 99%